冲之鸟礁是否应有大陆架？——200海里以外大陆架划界案中无居民岛礁的对比研究 - 丘君; QIU Jun; 柳文华; LIU Wenhua (《中国海洋法学评论》编辑部, 2009)
丘君，国家海洋局海洋发展战略研究所副研究员。 柳文华，中国科学院地理科学与资源研究所陆地水循环及地表过程重点实验室博士。 【中文摘要】日本提交了200海里以外大陆架划界案，并以冲之鸟礁为基点主张专属经济区和200海里以外大陆架。部分国家和国际社会质疑日本此举的合法性，认为冲之鸟礁属《联合国海洋法公约》第121条第3款定义的岩礁，不应拥有专属经济区和大陆架，不应主张200海里以外大陆架。冲之鸟礁的案例引起国际社会对有关岛礁划定200海里以外大陆架的权利基础问题的关注和讨论。目前已提交 的51个划界案中涉及多个利用无居民岛礁主张大陆架的案例，除冲之鸟礁以外，还包括澳大利亚的毕晓普和克莱克岛、麦克唐纳群岛，新西兰的邦蒂群岛，所罗门群岛的法图塔卡岛以及塞舌尔的鸟岛等。本文将对比分析这些无居民岛礁本身的基本情况，大陆架界限委员会审议这部分划界案的情况，以及其他国家和国际社会对沿海国利用这些岛礁主张200海里以外大陆架的反应，以判断冲之鸟礁可否主张200海里以外大陆架。 【Abstract】In November 2008, Japan submitted information on the limits of its continental shelf beyond 200 nautical miles to the Commission on the Limits of the Continental Shelf (Commission); the application included a claim to establish the Okinotori Reef as a base point which would be entitled to an exclusive economic zone (EEZ) and a continental shelf extending beyond 200 nautical miles. Japan's actions were challenged by members of the international community, which think that the Okinotori Reef should be considered a rock under article 121(3) of United Nations Convention on the Law of the Sea, and therefore should not be entitled to any EEZ，continental shelf or continental shelf beyond 200 nm. This case has drawn international attention and given rise to discussions on the determination of the outer limits of the continental shelf of uninhabited islands. Of the 51 submissions that the Commission has received thus far, several involve uninhabited islets, which include, besides the Okinotori Reef, the Bishop and Clerk Islets and the McDonald Islands of Australia, the Bounty Islands of New Zealand, Fatutaka Island of the Solomon Islands, and Bird Island of Seychelles. This article will compare the basic conditions of these uninhabited islets, the Commission's consideration of these submissions, and the responses of other countries and the international community to the use of these islets by coastal States to make claims for a continental shelf beyond 200 nm, in an attempt to judge whether the Okinotori Reef may make such a claim.